The Future Is Now: First Ideas on How Human Performance Improvement Is Going to Change. Issue 4 (April 2017) - Wittkuhn, Klaus D.
Abstract : Digitization will change our world at a speed and to an extent never experienced before. This will have a huge impact on how we must think about performance improvement and on how we do our job as performance improvement professionals. This article highlights some of the developments and their impact on performance and raises open questions. Finally, it drafts a framework meant to systematically guide our thinking about the changes we will face.